Implementation Marketing Business Plan for Electric Vehicle Charging Station (EV-Station) in Indonesia - Hendy Radja Willyanto; Muhammad Dhafi Iskandar (Syntax Idea)
The rapid growth in the use of electric vehicles (EVs) requires adequate infrastructure, including electric vehicle charging stations (SPKLU). To promote the adoption of electric vehicles and increase the use of SPKLU, careful marketing planning is needed by taking into account the elements of marketing mix (product, price, place, and promotion) as well as segmentation, targeting, and positioning (STP) practices, This study aims to develop a comprehensive marketing plan for SPKLU by integrating elements of marketing mix and STP approach. This research also seeks to understand how to identify the most relevant target segments, determine SPKLU's position in the market, and design marketing messages that suit those segments. The results of the study present an in-depth understanding of the preferences and needs of the target segment, as well as the factors influencing the decision to use SPKLU. These findings are used to formulate a marketing mix strategy that includes competitive pricing, strategic SPKLU location, promotion through various channels, and development of services that meet customer needs, The results of the study present an in-depth understanding of the preferences and needs of target segments, as well as factors that influence the decision to use SPKLU. These findings are used to formulate a marketing mix strategy that includes competitive pricing, strategic SPKLU locations, promotion through various channels, and service development that meets customer needs.